The Effects Of The Russian-ukrainian War On Algeria's Oil Exports - Bekhiti Ali (جامعة الوادي University of Eloued, 2024)
This study aims to show the impact of the Russian-Ukrainian war on Algeria’s oil exports, due to its contribution to increasing production. The economic situation in Algeria before the war and during the war, in addition to an analytical measurement study using the ACP model, A period of one year was chosen for the study, 6 months before the war and 6 months during the war, where the study concluded that the Russian-Ukrainian war had a positive impact on increasing exports of Algerian oil.
Keywords: The Russian-Ukrainian wa; Algerian oil exports; Algerian-Russian relations; Algerian-Ukrainian relation